2005
DOI: 10.1002/chin.200531262
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Death Comes Full Circle: Targeting Plasmid Replication in Drug‐Resistant Bacteria

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…It has been suggested that activation of TA systems could be an attractive antimicrobial strategy, as the released toxin would kill the host bacterial cell DeNap & Hergenrother, 2005;Gerdes et al, 2005;Alonso et al, 2007;Williams & Hergenrother, 2008). While the presence of TA systems in sequenced prokaryotic genomes has been established, before this work the prevalence of TA systems in clinical isolates of MRSA and PA was unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that activation of TA systems could be an attractive antimicrobial strategy, as the released toxin would kill the host bacterial cell DeNap & Hergenrother, 2005;Gerdes et al, 2005;Alonso et al, 2007;Williams & Hergenrother, 2008). While the presence of TA systems in sequenced prokaryotic genomes has been established, before this work the prevalence of TA systems in clinical isolates of MRSA and PA was unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Exploitation of the inherent toxicity of TA systems has been proposed as a novel antibacterial target, as activation of the latent toxin via direct TA complex disruption or some alternative mechanism would result in bacterial cell death DeNap & Hergenrother, 2005;Alonso et al, 2007;Williams & Hergenrother, 2008). However, a prerequisite for the success of this strategy is the identification of clinically important bacteria that would be susceptible to a compound that activates TA systems.…”
Section: Introductionmentioning
confidence: 99%
“…Identification and classification of plasmids should be based on genetic traits that are present and constant. These criteria are best met by traits concerned with plasmid maintenance, especially replication controls (DeNap and Hergenrother, 2005). In 1971 Datta and Hedges proposed a plasmid classification scheme based on the stability of plasmids during conjugation, a phenomenon called plasmid incompatibility (Datta and Hedges, 1971).…”
Section: Detection and Classification Of Plasmids Carrying Esbl And/omentioning
confidence: 99%
“…49,50 Furthermore, antibiotic nonsusceptibility is not always a clear one-to-one relationship between antibiotic exposure and resistance to that same antibiotic, but is likely complicated by bacterial acquisition of plasmids that often confer resistance to multiple antibiotics. [51][52][53] Finally, macrolide use in the private clinics may have contributed to penicillin resistance despite low levels of reported penicillin use. [54][55][56] S. pneumoniae serotypes/groups 19, 23, and 6 were the most commonly isolated, and a small percentage of each group was nonsusceptible to all four antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%